Foreign Direct Investment in sub-Saharan Africa : sustainability perspective - Hering, Leea (My University, 2025)
The significance of the Global South is growing in the global economy. Sub-Saharan Africa (SSA), that consists mostly of developing countries, is going through a huge change process as it is more strongly becoming an important part of the global economic system. This is happening mostly through foreign direct investment (FDI). There are various motives that makes multinational enterprises (MNEs) invest in SSA. This thesis discusses the location specific advantages of the OLI-framework to describe the drivers of FDI. Findings indicate that among others, strong institutions are attracting FDI, and they are also a necessity for sustainable FDI. FDI can be seen both as a sustainability promoting or a sustainability hindering phenomenon. This thesis compares modernization theory and dependency theory, that describe the dual pathways of development in the developing country. Modernization theory suggests that the host country develops through positive spillover effects, whereas dependency theory suggests that there is still an eminent exploitative relation between developed and developing countries. Since SSA has historically suffered from exploitation, unsustainable structures are common especially in resource rich countries. In countries with a one-sided economy structure, natural resource dependency and tendency for rent-seeking, a shift towards sustainable development is challenging. However, if host countries succeed strengthen institutions, attract MNEs that follow the triple bottom line (TBL), and commit to the sustainable development goals (SDGs), sustainability is much easier to achieve.

Globaalin etelän merkitys maailmantaloudessa kasvaa. Suurimmaksi osaksi kehittyvistä maista koostuva Saharan eteläpuolinen Afrikka käy läpi valtavaa muutosprosessia, kun siitä tulee yhä tärkeämpi osa maailmanlaajuista talousjärjestelmää. Tämä tapahtuu pääasiassa ulkomaisten suorien sijoitusten kautta. Moni asia motivoi monikansallisia yrityksiä investoimaan Saharan eteläpuoliseen Afrikkaan. Tämä tutkielma käsittelee OLI-viitekehyksen sijaintikohtaisia etuja kuvatakseen ulkomaisten suorien sijoitusten ajureita. Löydökset indikoivat, että muun muassa vahvat instituutiot houkuttelevat ulkomaisia suoria sijoituksia, ja nämä ovat myös edellytys kestäville investoinneille. Ulkomaiset suorat sijoitukset voidaan nähdä kestävää kehitystä edistävänä tai haittaavana ilmiönä. Tämä tutkielma vertailee modernisaatioteoriaa ja riippuvuusteoriaa, jotka kuvaavat kehittyvien maiden kehitystä kahdesta näkökulmasta. Modernisaatioteorian mukaan kehittyvä maa kehittyy positiivisten sivuvaikutusten kautta, kun taas riippuvuusteorian mukaan kehittyneiden ja kehittyvien maiden välillä vallitsee riistävä suhde. Koska Saharan eteläpuolinen Afrikka on historiallisesti kärsinyt riistosta, kestämättömät rakenteet ovat yleisiä erityisesti luonnonvaroiltaan rikkaissa maissa. Maissa, jossa on yksipuolinen talousrakenne, luonnonvarariippuvuutta ja taipumusta päättäjien välistävetoon, muutos kohti kestävää kehitystä on haastava. Toisaalta, jos valtio pystyy vahvistamaan instituutioitaan, houkuttelemaan kolmoistilinpäätöstä noudattavia monikansallisia yrityksiä ja sitoutumaan kestävän kehityksen tavoitteisiin, on kestävän kehitys huomattavasti helpompi saavuttaa.
Keywords: foreign direct investment, sub-Saharan Africa, triple bottom line, sustainable development goals, modernization theory, dependency theory